Implementation of Spirituality-Crisis Counseling to Reduce Early Childhood Trauma: Array - Dwi Bhakti Indri M (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
Events that left deep wounds has the potential to make people experiencing trauma. This matter cannot be separated in early childhood. Trauma in early childhood affects many different aspects of the development, both cognitive development, motor and socio-emotional. Spirituality-crisis counseling is a counseling service in the form of play therapy which integrated with the element of spirituality in its intervention. The goal is to reduce traumatic early childhood. This article attempts to explain the urgency of spirituality-crisis counseling in reducing traumatic early childhood.